Ecological influences in the biogeography of the Austral sedges - Viljoen, Jan-Adriaan (Department of Biological Sciences, 2016)
The biogeographic history of a species is a result of both stochastic processes such as dispersal and habitat filters that determine where a population with a given set of biological requirements can become established. In this dissertation, I examine the geographical and ecological distribution of the sedge tribe Schoeneae in conjunction with its inferred speciation history in order to determine the pattern of dispersal and the environmental factors that have influenced establishment. The biogeographic reconstruction indicates numerous transoceanic dispersal events consistent with random diffusion from an Australian point of origin, but with a bias towards habitats with vegetation type and moisture regime similar to the ancestral conditions of the given subgroup (open and dry habitats in the majority of cases). The global distribution of the tribe also suggests a preference for low-nutrient soils, which I investigate at the local (microhabitat) scale by contrasting the distributions of the tribes Schoeneae and Cypereae on the Cape Peninsula along soil fertility axes. The relationships between the phenotypic traits of species and their soil nutrient levels are also examined to determine whether the coexistence of the two groups in the Cape can be attributed to differences in nutrient accumulation behaviour or strategy of biomass allocation to roots or structural organs vs. leaves. No robust patterns were observed to identify such adaptations or to distinguish the tribes ecologically, a result that is at least partly due to low statistical power in the data set collected, which constrains the analysis to the use of simple models less able to detect subtle patterns in the ecological history of these sedges.